Penerapan Akuntansi Lingkungan Pada Perusahaan Industri di Kecamatan Tanjung Morawa - Indra Sukma Ramadhani; Ratna Sari Dewi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to determine and describe the state of the industrial company in Tanjung Morawa both in accounting and in the environment. This research uses literary research by looking at previous research with the available facts and then drawing conclusions. Using data collection techniques in this study, namely the study of documentation and qualitative descriptive data analysis techniques. The results of this study indicate that several industrial companies in Tanjung Morawa have implemented environmental accounting in their financial statements and based on the documentation that has been collected that largescale companies have recorded according to the standards. Only small companies and small industries do not apply environmental accounting